Dust penetrated quantitative classifcation of nearby barred spiral galaxies - Tailor, Asha (My University, 2012)
The objective of this dissertation is twofold. Firstly an extensive yet concise literature review on the state-of-the-art of near infrared barred spiral galaxy classi cation is presented. Secondly, two quantitative approaches to galaxy classi cation at near infrared wavelengths, the relative gravitational torque method and the isophotal ellipse tting method, are applied for the rst time to a sample of selected Spitzer IRAC nearby barred galaxies. Maximum relative gravitational torques are derived for a sample of 40 nearby bright barred disk galaxies at 3.6 m and 4.5 m. These torques are compared between galaxy pairs at these passbands and we nd an excellent agreement between the 3.6 m and 4.5 m morphology. The sample used incorporates a wide range of inclination and bar strength values. The tight coupling of 3.6 m and 4.5 m morphology provides an opportunity to classify intermediate redshift galaxies that have their near-infrared rest frame emissions shifted red-ward to 4.5 m; i.e.: out to z = 0:25. We nd a greater frequency of higher maximum relative torques in our sample compared with either Block et al. (2002) or Buta et al. (2004) due to sample bias, as this dissertation is aimed at understanding quantitative methods in classifying barred galaxies. Furthermore, we compare results from applying an isophotal ellipse tting technique and a gravitational torque analysis to a common sample of 28 nearby barred S4G/Spitzer galaxies imaged at 3.6 m. These two quantitative bar strength methods are applied to images that have identical orientation and deprojection parameters for an objective comparison. We nd a strong correlation between the gravitational torque and isophotal ellipse tting methods which in principle supports a method for estimating bar potentials out to intermediate redshifts by using an isophotal ellipse tting approach. This has important implications for bar-fraction estimates and galaxy accretion/evolution scenarios.
Keywords: Spiral galaxies.; Barred galaxies - Congresses.